2014
DOI: 10.5306/wjco.v5.i5.865
|View full text |Cite
|
Sign up to set email alerts
|

Tumour suppressor HLJ1: A potential diagnostic, preventive and therapeutic target in non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer-related mortality throughout the world. Non-small cell lung cancer (NSCLC) accounts for 85% of all diagnosed lung cancers. Despite considerable progress in the diagnosis and treatment of the disease, the overall 5-year survival rate of NSCLC patients remains lower than 15%. The most common causes of death in lung cancer patients are treatment failure and metastasis. Therefore, developing novel strategies that target both tumour growth and metastasis is an important an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 100 publications
(124 reference statements)
0
19
0
Order By: Relevance
“…Research studies have reported that HLJ1, targeting HSP 40, shows promising dual anti‐cancer effects, inhibiting both tumour growth and metastasis in non‐small cell lung cancer (NSCLC) (Tsai et al . ). HSP27 (HSPB1), a member of the small HSP family, is also overexpressed in many types of cancer, and targeting HSP27 has shown very promising results (Hayashi et al .…”
Section: Tumour‐associated Antigens For Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…Research studies have reported that HLJ1, targeting HSP 40, shows promising dual anti‐cancer effects, inhibiting both tumour growth and metastasis in non‐small cell lung cancer (NSCLC) (Tsai et al . ). HSP27 (HSPB1), a member of the small HSP family, is also overexpressed in many types of cancer, and targeting HSP27 has shown very promising results (Hayashi et al .…”
Section: Tumour‐associated Antigens For Cancermentioning
confidence: 97%
“…While HSP90 is eventually required for the formation of client proteins, other HSP family members all play essential roles in protein folding. Research studies have reported that HLJ1, targeting HSP 40, shows promising dual anti-cancer effects, inhibiting both tumour growth and metastasis in non-small cell lung cancer (NSCLC) (Tsai et al 2014). HSP27 (HSPB1), a member of the small HSP family, is also overexpressed in many types of cancer, and targeting HSP27 has shown very promising results (Hayashi et al 2012), but currently no clinical trial has passed phase III (Katsogiannou et al 2014).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…In China, the incidence of lung cancer in the past few decades has doubled due to the aging population, smoking and decline in air quality (4). Although some treatments have achieved certain therapeutic effect, the overall 5-year survival rates of NSCLC patients is still below 15% (5). Most NSCLC patients are in mid-term and advanced stage when diagnosed, which could contribute its poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the main cause of cancer‐related death worldwide. Among all cases of lung cancer, 85% are non–small cell lung cancer (NSCLC), which is associated with an overall 5‐year survival rate of below 15% . About 50% to 80% of lung cancer patients suffer from chronic obstructive pulmonary disease (COPD), and the risk of lung cancer in COPD is estimated as up to 167 per 10 000 person‐years …”
Section: Introductionmentioning
confidence: 99%